2020
DOI: 10.1177/1048371320942279
|View full text |Cite
|
Sign up to set email alerts
|

Modern Band and Special Learners

Abstract: For the greater part of the past 50 years, music educators have advocated for contemporary approaches to music education that reflect the interests of students. This has recently manifested in an approach to music education that scholars call Modern Band. Though the term lacks any one definition, Modern Band classes typically involve popular music making with guitars, drum set, electric bass, and keyboard. Among the features of this approach is a student-centered orientation that is focused on the individual l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…The modern band teachers surveyed by Randles (2018) also reported that 66% (n = 503) of their modern band programs allowed students to choose some of the songs that they performed, whereas 72% (n = 549) of teachers indicated that their students have performed their favorite music in public. These findings are supported by other researchers that highlighted the prevalence of songs chosen by the students in modern band classes (Knapp, 2020;Vasil et al, 2017).…”
Section: Perspectives Of Modern Band Teacherssupporting
confidence: 86%
See 3 more Smart Citations
“…The modern band teachers surveyed by Randles (2018) also reported that 66% (n = 503) of their modern band programs allowed students to choose some of the songs that they performed, whereas 72% (n = 549) of teachers indicated that their students have performed their favorite music in public. These findings are supported by other researchers that highlighted the prevalence of songs chosen by the students in modern band classes (Knapp, 2020;Vasil et al, 2017).…”
Section: Perspectives Of Modern Band Teacherssupporting
confidence: 86%
“…Some scholars view formal and informal learning practices as two poles of a continuum, and argue that learning activities can fall anywhere on that continuum based on the situation, learning style, ownership of the activity, and intentionality (Folkestad, 2006; Green, 2002). Knapp (2020) argued that since the modern band approach is based on informal learning theory, “it is free from the predetermined curricular constraints that limit typical music education models like band, chorus, and orchestra” (p. 3). According to Knapp, teachers are thus able to design and adjust their lessons based on the needs of their classroom and the interests of students.…”
Section: Informal Learning and Nonformal Teaching In The Modern Band Classroommentioning
confidence: 99%
See 2 more Smart Citations
“…Further deepening ties between these two organizations, and in the process muting any disruptiveness of LKR, NAfME frequently publishes articles on modern band in its research and practitioner journals (e.g. Burstein and Powell, 2019;Knapp, 2020;Powell, 2021;Vasil et al, 2019). Furthermore, as of January 2022, there is also a dedicated Modern Band Journal, a trade publication from artistpro, LLC (artistpro, 2022), which produces well regarded and widely read trade magazines to thousands of music teachers across the US.…”
Section: Lkr and Modern Band As Punk Problematicmentioning
confidence: 99%